MÃO DE FERRO NA CIDADE DO AÇO?: A política de segurança pública no âmbito do poder Executivo em Volta Redonda RJ no período entre 1988 e 2010 - Castro, Felipe da Matta de (2012)
Research on the history, organization and policy initiatives in the field of public safety in the city of Volta Redonda. As a methodological approach was chosen the period between 1988 and 2010, restricting the scope of analysis to the initiatives of the Executive Branch. Despite the delineation of the period to which the research is dedicated, the paper also points out some initiatives that have been and will be implemented after the year 2010. It seeks to investigate also the main lines of action of the organs of public security and the principles thereof. To understand the object of study, we conducted a historical review of the forms of state intervention in the face of demands and social pressures, political and social policies and recent discussions about public safety at the national level. Data analysis is still done with data provided in interviews with scholars and with social themes relevant to public safety in Volta Redonda. This study also has the intention to become a record of policy development for public safety in Volta Redonda and thereby contribute to the account of the history of the council and other public safety discussions